Development and reliability of test to measure perceptual-motor performance in combat sports: the Striking Reaction Time Task (SRTT) (Revista de Artes Marciales Asiáticas, 2025)
The perceptual-motor performance of 15 professional mixed martial arts (MMA) athletes was evaluated using the Striking Reaction Time Task (SRTT). Six LED sensors equipped with motion sensors, controlled by a smartphone application, were attached to specific anatomical targets on a human-like figure using a body opponent bag (BOB). The SRTT consisted of two blocks: SRTT-Simple, where one LED sensor was illuminated at a time, and SRTT-Complex, where all six LED sensors were illuminated, with the target sensor highlighted in a different color. Each block included 120 stimuli. The intraclass correlation coefficient (ICC), coefficient of variation (CV), and minimal detectable change (MDC) of reaction time (RT) were analyzed. Perceptual-motor performance, measured by RT, varied according to the stimulus type, with SRTT-Complex tasks resulting in longer RTs compared to SRTT-Simple tasks for all strikes except hooks. All strikes demonstrated good to excellent reliability, with ICC values ranging from 0.76 to 0.96 (95% CI: 0.62–0.98), CV values between 11% and 17%, and MDC values ranging from 47 to 136 ms, depending on the strike and stimulus type. These findings suggest that the SRTT is a reliable tool for assessing sport-specific perceptual-motor performance in striking combat sports. Future studies should investigate its sensitivity in distinguishing between non-athletes and athletes of varying skill levels, as well as its responsiveness to training interventions.